2001
DOI: 10.2337/diabetes.50.2007.s160
|View full text |Cite
|
Sign up to set email alerts
|

beta-cell dysfunction and failure in type 2 diabetes: potential mechanisms.

Abstract: Type 2 diabetes is characterized by a progressive loss of ␤-cell function throughout the course of the disease. The pattern of loss is an initial defect in early or firstphase insulin secretion, followed by a decreasing maximal capacity of glucose to potentiate all nonglucose signals. Last, a defective steady-state and basal insulin secretion develops, leading to complete ␤-cell failure requiring insulin treatment. This functional loss exceeds the expected impact of a 20-50% loss of ␤-cells reported at autopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
196
0
5

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(204 citation statements)
references
References 25 publications
3
196
0
5
Order By: Relevance
“…Such a defect is indicative of a progressive insensitivity of the b-cell to glucose (Porte and Kahn, 2001). Even though insulin secretion in response to glucose ingestion is blunted in long-standing type 2 diabetes patients, we have shown that co-ingestion of a protein hydrolysate/leucine mixture can stimulate endogenous insulin secretion resulting in a 2-4-fold greater postprandial insulin response (van Loon et al, 2003;Manders et al, 2005Manders et al, , 2006a.…”
Section: Introductionmentioning
confidence: 72%
“…Such a defect is indicative of a progressive insensitivity of the b-cell to glucose (Porte and Kahn, 2001). Even though insulin secretion in response to glucose ingestion is blunted in long-standing type 2 diabetes patients, we have shown that co-ingestion of a protein hydrolysate/leucine mixture can stimulate endogenous insulin secretion resulting in a 2-4-fold greater postprandial insulin response (van Loon et al, 2003;Manders et al, 2005Manders et al, , 2006a.…”
Section: Introductionmentioning
confidence: 72%
“…Individuals with type 2 diabetes mellitus (T2DM) have impaired b-cell function, which leads to reduced or absent first phase and curtailment of the second phase in postprandial blood insulin levels (Porte & Kahn 2001). In addition, the normal rhythmic variations in blood insulin levels are replaced by irregular or lost insulin oscillations (Lang et al 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with non-diabetic individuals, those with diabetes are two to three times more likely to have a CV event; moreover, the proportion of people with diabetes who will die from cardiovascular causes is >70% [2]. Epidemiological and mechanistic explanations that have been proposed to account for this strong relationship include: (1) prolonged exposure to hyperglycaemia and its consequences [3]; (2) antecedent and concurrent insulin resistance [4,5]; (3) effective insulin deficiency [6]; (4) associated lipid and blood pressure abnormalities [7]; and (5) an as yet undefined determinant of both diabetes and CV disease. Varying proportions of individuals with diabetes manifest one or Listed by country in References 13 and 15. more of these abnormalities; however, as diabetes is defined on the basis of an elevated glucose level, everyone with diabetes has a history of hyperglycaemia.…”
Section: Introductionmentioning
confidence: 99%